Photon, proton, and neutron shielding capacity of optical tellurite-vanadate glass systems: Theoretical investigation. (July 2021) - Rammah, Yasser S.; Olarinoye, I.O.; El-Agawany, Fouad I.; El-Adawy, Amin; Yousef, El Sayed
Abstract: The influence of density and molar concentration of Ag2 O on photon, proton, neutron, and alpha particle shielding capacity of tellurite-vanadate-silver glass systems with the form 40TeO2 +(60-x)V2 O5 +xAg2 O: x = 0–50 mol% (encoded as TVAg0- TVAg50) was evaluated and analyzed in a wide range of energy (0.015–15 MeV). Linear and mass attenuation coefficients ( μ, μ m ), half value thickness (HVT), mean free path (MFP), and effective atomic number ( Z eff ) were evaluated via the free online program–Phy-X/PSD, while EBF and EABF were computed via EXABCal software. The maximum μ m was obtained at the least photon energy (15 keV) with values equal to 29.702, 31.371, 32.949, 34.443, 35.86, and 37.205 cm 2 g -1 for TVAg0, TVAg10, TVAg20, TVAg30, TVAg40, and TVAg50, respectively. Generally, The μ m of the glass's trends in the order: ( μ m )TVAg0  < ( μ m )TVAg10  < ( μ m )TVAg20  < ( μ m )TVAg30  < ( μ m )TVAg40  < ( μ m )TVAg50 . The trend of μ amongst the glasses is like that of the mass attenuation coefficient. The values of the maximum MFP varied from 9.757 to 4.53 cm for TVAg0 and TVAg50, respectively. The HVT trend of TVAg-glasses obeys the order: (HVT)TVAg0  > (HVT)TVAg10  > (HVT)TVAg20  > (HVT)TVAg30  > (HVT)TVAg40  > (HVT)TVAg50 . The range of Z e f f for the glasses varied from: 14.8 to 42.38 for TVAg0 glass and from 26.06 to 47.63 for TVAg50 glass. The f -factor of the TVAg-glasses were lower than unity except that of TVAg50 at 5 MeV. The variations in buildup factors with photon energy is alike for all glass materials and depth of penetration (mfp). The projected range (PR) followed the order: (PR)TVAg0  > (PR)TVAg10  > (PR)TVAg20  > (PR)TVAg30  > (PR)TVAg40  > (PR)TVAg50 for both proton and α-particle. Mass stopping power (MSP) is inversely proportional to the atomic number of the target (TAVg-glasses). Results confirmed that density and molar concentration of Ag2 O plays an important role for improving the radiation shielding capacity of the investigated TAVg-glasses. Highlights: Samples of tellurite-vanadate-silver glasses were chosen. Gamma radiation shielding features were evaluated via Phy-X/PSD program. EBF and EABF were computed via EXABCal software. Results were compared with previous ones.